PERJANJIAN ANTARA PEMERINTAH DENGAN PIHAK SWASTA DALAM KAITANNYA DENGAN DIVESTASI SAHAM PT.NNT di NUSA TENGGARA BARAT - Zainal Asikin (Masalah-Masalah Hukum, 2013)
Abstract The research analyzes about how the Indonesian Law regulates on shares divestment and how the divestment practice conducted by Local government of West Nusa Tenggara.Through the normative approach (normative study) and case approach. It was concluded that the law in Indonesian has not regulated, the process of shares divestment by the Government (Local Company). However Trough the Legal analogy method so the Acts Number 1 Year 2004 on State treasury and some of its implementation regulations applicable to the investments and divestments process. Likewise, as long as the divestment cooperation aims to build the public infrastructure so that the President Regulation Number 65 Year 2005 refers to President Number 13 Year 2010 could be umbrella of law.In the process of shares divestment of PT. NNT, it is found that there were procedural mistakes by the Government of West Nusa Tenggara, as well as there was collaboration agreement contain a conflict of norm, so that it has potential of loss to the state. Keywords:  the Cooperation Agreement, Divestiture Shares Abstrak Penelitian ini mengkaji bagaimana hukum di Indonesia mengatur tentang divestasi saham dan bagaimana praktek divestasi saham itu dilakukan oleh pemerintah Daerah Nusa Tenggara Barat. Dengan melalui pendekatan normatif (studi normative)  dan pendekatan kasus, maka disimpulkan bahwa hukum di Indonesia belum mengatur tentang proses divestasi saham oleh pemerintah ( Perusahaan Daerah). Akan tetapi melalui metode analogi hukum maka UU No.1 Tahun 2004 tentang Perbendaharaan Negara dan beberapa peraturan pelaksanannya dapat diterapkan terhadap proses investasi dan divestasi. Begitupula sepanjang yang menyangkut kerjasama divestasi itu bertujuan untuk membangun infrastruktur publik maka Perpres No.67 tahun 2005 jo Perpres No.13 Tahun 2010 dapat dijadikan payung hukum. Ditemukan kesalahan prosedur dalam proses divestasi saham PT.NNT oleh Pemerintah NTB dan adanya perjanjian Kerjasama yang mengandung konflik norma sehingga berpotensi merugikan Negara (daerah) Kata Kunci: Perjanjian Kerjasama, Divestasi Saham